The passing of the Dominant Paradigm - Gideon de Wet (Communicare)
In this paper an attempt is made to contribute towards a better understanding regarding the role and application of mass media (TV) with reference to developmental efforts. A theoretical and explorative overview will be posed deal Ing with three interlocking areas: 1. A retrospective analysis and discus sion of Rogers' (1976) article on "Communication and Development: The Passing of the Dominant Paradigm." An attempt is made, in an Integrated fashion, to analy, the Im plications of Rogers' (1976) declara tion that the dominant paradigm has passed. 2. Secondly, and as a result of serious methodological questions regarding the analysis and Interpretion of developmental communication ef forts, an attempt is made to pose theoretical considerations which can lead to the structuring of an alter native developmental approach with reference to rural development. 3. The third area, which could be regard ed as a natural consequence of the above-mentioned, deals with the role of the mass media (TV) with reference to rural development. The analysis In cludes an overview on media Involve ment in development as well as the specific applicability of "big media" in "little worlds". The emphasis shifts to message content where the impor tance of cultural values and the cultural convergence of messages is emphasised.